The relationship between the professional values and care behaviors of surgical nurses in Turkey - Çelik Bekleviç, Arzum; Çelik, Sevim (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. The professional values and the care behaviors of surgical nurse’s play an important role in providing quality patient care and increasing patient satisfaction. The aim of this study was evaluated the relationship between the professional values and care behaviors of surgical nurses. Material and methods. This descriptive and correlational study consisted of 245 surgical nurses working in Turkey. Data were collected using a Personal Information Form, the Nurses Professional Values Scale, and the Caring Behaviors Inventory-24. Results. The NPVS total mean score of the surgical nurses was 118.26. The CBI-24 total mean score of the surgical nurses was 5.25. The nurses obtained high mean scores in both the Nurses Professional Values Scale and subscales, and the Caring Behavior Inventory-24 and subscales. A weak, positive and significant relationship was found between the professional values and care behaviors of the surgical nurses (p<0.001). Both the individual and professional characteristics of the surgical nurses affected their perceptions of professional values and care behaviors (p<0.05). Conclusion. The study showed that they had high perceptions of professional values and caring behaviors and adopted at most human dignity from professional values. Personal and organizational activities should be carried out to improve the professional values of surgical nurses and have them internalize care behaviors.
Ethical approval to conduct the study was obtained from the Human Research Ethics Committee of Zonguldak Bulent Ecevit University (decision number:373, Decision date: 29.05.2018). Informed consent was obtained from the surgical nurses participating in the study.
Keywords: care behaviors; professional values; surgical nursing